2006
DOI: 10.1037/0022-006x.74.5.797
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analytic review of benefit finding and growth.

Abstract: The authors conducted a meta-analysis to examine the relations of benefit finding to psychological and physical health as well as to a specific set of demographic, stressor, personality, and coping correlates. Results from 87 cross-sectional studies reported in 77 articles showed that benefit finding was related to less depression and more positive well-being but also more intrusive and avoidant thoughts about the stressor. Benefit finding was unrelated to anxiety, global distress, quality of life, and subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

190
1,551
34
77

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,554 publications
(1,885 citation statements)
references
References 102 publications
(49 reference statements)
190
1,551
34
77
Order By: Relevance
“…These findings are consistent with the results of a recent meta-analytic study of post-traumatic growth after a variety of traumatic events (Helgeson et al, 2006), which reported that women typically perceive more benefits from a traumatic event; potentially, this is related to how women cope with the experience. The importance of time since death in relation to identifying post-traumatic growth is also potentially supported by Helgeson and colleagues (2006), who identified that benefit-finding was strongly related to less depression and greater positive affect when considering parents two years after a trauma.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…These findings are consistent with the results of a recent meta-analytic study of post-traumatic growth after a variety of traumatic events (Helgeson et al, 2006), which reported that women typically perceive more benefits from a traumatic event; potentially, this is related to how women cope with the experience. The importance of time since death in relation to identifying post-traumatic growth is also potentially supported by Helgeson and colleagues (2006), who identified that benefit-finding was strongly related to less depression and greater positive affect when considering parents two years after a trauma.…”
Section: Discussionsupporting
confidence: 91%
“…There is no documentation of whether the same relationship occurs at times closer to the event. Furthermore, this review supports Helgeson et al’s (2006) findings which documented that it was not possible, based on current evidence, to draw conclusions in relation to the nature of the stressor in understanding benefit-finding. Perhaps this is because understanding how individuals make sense of the experience is more important than the event itself.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations